SENI BATIK MEGAMENDUNG CIREBON DAN PENGARUHNYA TERHADAP SENI MODE DI INDONESIA - Menul Teguh Riyanti (Universitas Trisakti, 2012)
AbstractBatik is one of Indonesia's cultural heritage products. along with the times, many batik patterns change, functions and there is a touch of other cultures. On his general decoration I style batik following forms of natural phenomena, or objects of even;day experience. Example is the megamendung of batik patterns that follow the natural phenomenon, because the motive in the form of batik Cirebon cloud. Technique done in two babaran. First at babar cloth with red, at batik again later dyed blue, and even, sometimes dyed with yellow color (tageran). So would happen crosses the color red, blue, black, and green with a white base, now there is the color of the manufacturer or synthetic colors that enrich the color of the overcast cloud batik. Fashion art at this time, many apply batik in everyday clothing, formal or informal. Because batik bet is interesting, unique and have artistic value of the image height. Presence of batik fashion design has been with the times is expected to strengthen the textile and batik as an original Indonesian art and culture. AbstrakBatik merupakan salah satu warisan produk budaya Indonesia. Seiring dengan perkembangan zaman, batik banyak mengalami perubahan corak, fungsi serta terdapat sentuhan dari budaya lain. Pada umumnya ragam hias/corak batik mengikuti bentuk-bentuk gejala alam, atau benda-benda yang dialami sehari-hari, contohnya adalah corak batik mega mendung yang mengikuti gejala alam karena motifnya yang berbentuk awan. Teknik pembuatan batik Cirebon dikerjakan dalam dua kali babaran. Pertama-tama kain itu dibabar dengan warna merah, dibatik lagi kemudian dicelup dengan warna biru bahkan kadang kala dicelup dengan warna kuning (tageran). Demikian akan terjadi persilangan warna